2022
DOI: 10.1177/15579883221092290
|View full text |Cite
|
Sign up to set email alerts
|

Allostatic Load, Income, and Race Among Black and White Men in the United States

Abstract: Research indicates that income is significantly associated with allostatic load (AL) and that this association may differ between White and Black Americans. Most existing income–AL link work focuses on women and less is known about this association among men. Using data from the National Health and Nutrition Examination Survey (NHANES), we examined whether race moderates the association between income and AL among Black and White men in the United States ( n = 5,685). We find that, regardless of income levels,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In our cohort Black men are as likely as Black women to have suffered from this condition. Studies document a disproportionate burden of psychosocial stressors and allostatic load on Black men in the US 22 . Resultantly, Black men may be at higher risk for MINOCA and recurrent angina than White men, and a higher burden of psychosocial stressors may be causative.…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort Black men are as likely as Black women to have suffered from this condition. Studies document a disproportionate burden of psychosocial stressors and allostatic load on Black men in the US 22 . Resultantly, Black men may be at higher risk for MINOCA and recurrent angina than White men, and a higher burden of psychosocial stressors may be causative.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been used previously [ 31 ]. The literature has reported differences in morbidity and mortality when allostatic load scales reached above 3 or 4, so we used the cut point (AL≥4) that has been used widely; the binary variable sowed the “elevated AL” (if ALS≥4 as 1) [ [32] , [33] , [34] , [35] , [36] , [37] ]. We used this binary variable to run the modified Poisson regression models.…”
Section: Methodsmentioning
confidence: 99%
“…Some evidence offers that excessive exposure to psychosocial factors such as stressful life events, discrimination, racism, John Henryism (a high effort coping style towards upward mobility that incurs wear and tear on bodies and detected as poor cardiometabolic health) (Brody et al, 2018; James, 1994), medical mistrust, and limited access to care are reasons for NHB men's distinct hypertension burden (Blyler & Rader, 2019; Control & Prevention, 2010; Subramanyam et al, 2013). One study found that NHB men have a higher prevalence of allostatic load (a chronic stress measure that incorporates blood pressure) than NHW men with the same level of education (Tavares et al, 2022). This study suggests that SES alone may not protect NHB men's health.…”
mentioning
confidence: 99%